ANALISIS PERENCANAAN STRATEGI PADA PT IDEA IMAJI PERSADA DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF - William Wijaya; Laura Lahindah; Henry Henry (Center for Economic Studies Universitas Katolik Parahyangan, 2020)
The advertising industry is an industry that has experienced a significant increase due to the shift in this industry to a digital-based business model. The role of digital agencies is very important, because most companies market their products digitally. This condition causes many digital agencies to emerge that are trying to meet market demand, causing the digital agency business to be faced with increasingly fierce competition. Strategic planning is a systematic process agreed by the organization and builds engagement among key stakeholders about priorities for its mission and responsiveness to the operating environment. With strategic planning, the organization can increase its competitive advantage in the face of its competitors. This research was conducted at PT Idea Imaji Persada Bandung. The research method used is the descriptive qualitative method. Data collection in this study was conducted by conducting interviews with top management and middle management at PT Idea Imaji Persada, observations, documentation studies, and literature studies. The strategic design phase consists of three stages: strategy formulation, strategy implementation, and strategy evaluation. By using the TOWS matrix, the results of the strategy design produce seven strategic designs, namely, creating a community with digital agencies in Bandung as a means of developing the digital agency industry, creating Idea Imaji apps for clients, or prospective clients, posting client testimonials on the PT Idea Imaji Persada, giving appreciation or rewards for employees who have good performance, developing tracking system software to control employee performance, benchmarking ideas on a regular basis with other agencies, also creating SOPs and service standardization. The strategy implementation process can be carried out in stages according to the company's conditions.